PROTECTION OF THE RIGHTS OF PERSONS WITH MENTAL DISABILITIES TO LIBERTY AND INFORMED CONSENT TO TREATMENT: A CRITIQUE OF GORDON MADDOX MWEWA & OTHERS V ATTORNEY-GENERAL & ANOTHER (African Disability Rights Yearbook, 2021)
This article appraises the judgment of the High Court of Zambia in the case of Gordon Maddox Mwewa & Others v Attorney-General & Another. The discussion of the judgment concerns the Court’s interpretation of the right of persons with disabilities to protection from involuntary detention and to informed consent to treatment. The judgment is analysed against international human rights standards on the rights of persons with disabilities to human dignity, informed consent to treatment, liberty and security of the person contained in the Convention on the Rights of Persons with Disabilities and international and comparative human rights jurisprudence on these rights. The authors argue that the Zambian High Court failed to properly apply constitutional principles on limitation of rights when it declined to declare unconstitutional Zambia’s Mental Disorders Act, which allows involuntary detention and forced treatment of persons with mental disabilities.